Системно-синергетична стратегія формування особистості cтудента-еколога - Кушнір, Світлана (Видавництво Львівської політехніки, 2012)
Формирование личности будущего эколога рассматривается с позиций синергетического влияния учебы и воспитания. The author considers the formation of future ecologist’s personality from the position of synergetic influence of training and education.
Системно-синергетическая стратегия формирования и развития личности студента-эколога
Systemic and synergetic strategy of the formation and development of future ecologist’s personality
Keywords: синергетика; личность; учебно-воспитательный процесс; экология; synergetics; personality; educational process; ecology